Koncepcja kontroli zarządczej w wybranej jednostce samorządu terytorialnego - Durbajło-Mrowiec, Małgorzata (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
For several years units of public finances, including units of self-government, have been obliged to use management control according to the law. It is one of the tools that should improve the efficiency of public funds spending. There are not many supporters of this system and its implementation is unsuccessful. Taking into account a specificity of a researched self-government unit the author suggested a model of management control that is adequate to the needs of the unit and a procedure of implementation where huge impact is put on management staff and workers training. Efficiency and efficacy of a system should guarantee task-oriented budget.
Keywords: management control finance; management internal audit